Hepatic‐specific lipin‐1 deficiency exacerbates experimental alcohol‐induced steatohepatitis in mice. Issue 6 (17th October 2013) - Hu, Ming; Yin, Huquan; Mitra, Mayurranjan S.; Liang, Xiaomei; Ajmo, Joanne M.; Nadra, Karim; Chrast, Roman; Finck, Brian N.; You, Min
<x xml:space="preserve">Abstract</x> Lipin‐1 regulates lipid metabolism by way of its function as an enzyme in the triglyceride synthesis pathway and as a transcriptional coregulatory protein and is highly up‐regulated in alcoholic fatty liver disease. In the present study, using a liver‐specific lipin‐1‐deficient (lipin‐1LKO) mouse model, we aimed to investigate the functional role of lipin‐1 in the development of alcoholic steatohepatitis and explore the underlying mechanisms. Alcoholic liver injury was achieved by pair feeding wild‐type and lipin‐1LKO mice with modified Lieber‐DeCarli ethanol‐containing low‐fat diets for 4 weeks. Surprisingly, chronically ethanol‐fed lipin‐1LKO mice showed markedly greater hepatic triglyceride and cholesterol accumulation, and augmented elevation of serum liver enzymes accompanied by increased hepatic proinflammatory cytokine expression. Our studies further revealed that hepatic removal of lipin‐1 in mice augmented ethanol‐induced impairment of hepatic fatty acid oxidation and lipoprotein production, likely by way of deactivation of peroxisome proliferator‐activated receptor γ coactivator‐1alpha, a prominent transcriptional regulator of lipid metabolism. Conclusions: Liver‐specific lipin‐1 deficiency in mice exacerbates the development and progression of experimental alcohol‐induced steatohepatitis. Pharmacological or nutritional modulation of hepatic lipin‐1 may be beneficial for the prevention or treatment of human alcoholic fatty liver disease. (Hepatology 2013; 58:1953–1963)